Modeling conflicts at work: The case of elementary school employees in Croatia - Katarina Kostelić; Morena Paulišić; Marli Gonan Božac (Administrative Sciences, 2023)
This paper aims to explore conflict as a process that includes antecedents, management strategy, and outcomes while examining the role of affective states in an elementary school working environment. After a theoretical overview and systematization of the conflict elements, a questionnaire was developed that satisfies internal reliability and construct validity. Conflicts at the workplace were modeled with Bayesian SEM, and the results point out the prominent role of affective states in conflicts. Findings confirmed that (1) affective states affect the conflict management strategy choice; (2) different conflict management strategies lead to different conflict consequences; and (3) different affective states lead to differently perceived conflict consequences/outcomes. In addition, we conclude that conflicts with dominantly positive and negative affective states behave structurally differently. The revealed role of affective states facilitates future intervention possibilities in education about conflict management strategies and control of emotions and affective states. Raising awareness about affective states' role in the conflict might increase mutual un-understanding and contribute to a healthy school social environment as a safe space for learning, sharing ideas, and joint actions toward a common goal.
Keywords: 350; affective states; bayesian SEM; causes of conflict; conflict management strategies; conflict process; consequences of conflict; reliability; validity